Native Wildflowers: Mimosa strigillosa Torr. & A. Gray - Jeffrey G. Norcini; James H. Aldrich (EDIS, 2007)
ENH-1075, a 3-page illustrated fact sheet by Jeffrey G. Norcini and James H. Aldrich, describes two species of Mimosa that are native to Florida, use of powderpuff mimosa in the landscape, establishment, pests, and availability. Includes references. Published by the UF Department of Environmental Horticulture, November 2007.